Class II MOD restoration using bulk-fill flowable and natural layering resin composites: combining strengths in an extensive preparation - Durán Ojeda, Gerardo (2022)
The restoration of large class II MOD cavity preparations is a highly complex clinical scenario. Selecting correctly a composite resin and planning the stratification sequence will improve the adaptation of the composite resin masses and will control the polymerization shrinkage stress. In the following clinical case report, the step- by-step protocol of the combined use of an high-refractive-index enamel-like composite resin is shown for the restoration of lost marginal ridges and the occlusal surface, together with a low viscosity Bulk-Fill composite resin for dentine reconstruction in a highly damaged posterior tooth.